PERILAKU PENCARIAN INFORMASI MAHASISWA DALAM MEMENUHI KEBUTUHAN INFORMASI SEBELUM DAN SAAT PANDEMI COVID-19 - Muhammmad Nurfadillah; Ardiansah Ardiansah (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
The Covid-19 pandemic has brought changes to every aspect of life, one of which is education. Due to these circumstances, conventional learning has turned into online learning to avoid potential virus-spreading in university clusters, and UPI Library and Information Science 2019 students must follow the policy. The study aims to determine the information-seeking behavior of university students in meeting their information needs and differences in information-seeking behavior before and during the Covid-19 pandemic. This study method uses a descriptive quantitative research method. The sample of this research is students who experience two types of learning, conventional learning (in the classroom) and long-distance learning (online class). The results of this study indicate that there are differences in information-seeking behavior of UPI Library and Information Science 2019 students before and during the Covid-19 pandemic both in terms of motivation, place, sources, strategies, and obstacles in finding information. This is shown from the percentages of respondents' answers that show a decrease in physical activity such as visiting the library and a decrease in the use of printed media in finding information during the Covid-19 pandemic. On the other hand, the use of electronic and online-based media to search for information such as e-journal catalogs is increasing, and the use of electronic information sources has also increased during the Covid-19 pandemic.